Public Debt and Productivity : The Difficult Quest for Growth in Jamaica - Blavy, Rodolphe (IMF Working Papers; Working Paper ;, 2006)
The paper analyzes Jamaica's experience of low growth despite consistently high investment. Cross-country analysis provides evidence of a significant and negative relationship between total public debt and productivity growth. Looking at the specific channels through which high debt affects productivity growth and the allocation of resources in Jamaica, the study finds that high public debt has been associated with macroeconomic uncertainty and an output structure that relied excessively on a few maturing sectors with limited scope for productivity growth. Furthermore, public investment has been crowded out by debt service, further adversely affecting productivity growth.